2011
DOI: 10.1038/ncomms1248
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals vertebrate phylotypic period during organogenesis

Abstract: One of the central issues in evolutionary developmental biology is how we can formulate the relationships between evolutionary and developmental processes. Two major models have been proposed: the 'funnel-like' model, in which the earliest embryo shows the most conserved morphological pattern, followed by diversifying later stages, and the 'hourglass' model, in which constraints are imposed to conserve organogenesis stages, which is called the phylotypic period. Here we perform a quantitative comparative trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
306
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(362 citation statements)
references
References 32 publications
31
306
3
1
Order By: Relevance
“…Similar questions related to the conservation of developmental processes in the face of evolutionary morphological changes were previously asked in the context of modern and classic Evodevo (Haeckel and McCabe, 1912; von Baer, 1828; Gould, 1977; Riedl, 1978; Irie and Kuratani, 2011; Koyabu et al, 2011). …”
Section: Discussionmentioning
confidence: 85%
“…Similar questions related to the conservation of developmental processes in the face of evolutionary morphological changes were previously asked in the context of modern and classic Evodevo (Haeckel and McCabe, 1912; von Baer, 1828; Gould, 1977; Riedl, 1978; Irie and Kuratani, 2011; Koyabu et al, 2011). …”
Section: Discussionmentioning
confidence: 85%
“…These results indicate that lophophores share the molecular nature of the head and anterior centralized nervous system. Interestingly, many of these 'head/lophophore' genes overlap with those that are conservatively expressed during the organogenesis stage in vertebrates-the phylotypic period 44 , including foxG1, pax6, klf2, emx2 and islet1 (Supplementary Tables 29 and 30). Most of these genes are associated with neuronal differentiation, sensory organ development and forebrain development (Supplementary Table 29).…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…The functional relevance of nonconserved microRNAs is the subject of much debate, as they are often reported to be expressed at low levels or during restricted stages of development (Berezikov 2006;Chen and Rajewsky 2007;Liang and Li 2009;Meunier et al 2012;Roux et al 2012). Despite a general positive correlation between sequence conservation and expression, conservation of the protein-coding transcriptome is not uniform across different stages of development (Davis et al 2005;HazkaniCovo et al 2005;Cruickshank and Wade 2008;Roux and Robinson-Rechavi 2008;Domazet-Lošo and Tautz 2010;Kalinka et al 2010;Irie and Kuratani 2011;Kalinka and Tomancak 2012;Quint et al 2012). For example, the protein-coding transcriptome of adult animals has been shown to be less conserved than that of the embryo in both invertebrates and vertebrates (Domazet-Lošo and Tautz 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the protein-coding transcriptome of adult animals has been shown to be less conserved than that of the embryo in both invertebrates and vertebrates (Domazet-Lošo and Tautz 2010). This is suggested to be a consequence of significant canalization of particular cellular processes, deployed at specific developmental stages, which are less robust to the consequences of mutations (Davis et al 2005;Hazkani-Covo et al 2005;Cruickshank and Wade 2008;Roux and Robinson-Rechavi 2008;Domazet-Lošo and Tautz 2010;Kalinka et al 2010;Irie and Kuratani 2011;Kalinka and Tomancak 2012;Quint et al 2012). It has been suggested that microRNAs have birth and death dynamics distinct from protein-coding genes, and that they act as buffers contributing to canalization of developmental processes (Hornstein and Shomron 2006;Peterson et al 2009).…”
Section: Introductionmentioning
confidence: 99%